Contribution to the knowledge of Chinese Phasmatodea X: Eight new species of Cnipsomorpha from China (Phasmatidae: Clitumninae: Medaurini) - Ho, George Wai-Chun (Zootaxa, 2021)
Eight new species of Cnipsomorpha Hennemann, Conle, Zhang & Liu, 2008 are described from China. They are namely, Cnipsomorpha inflexa sp. nov., Cnipsomorpha jinpingensis sp. nov., Cnipsomorpha nigromaculata sp. nov., Cnipsomorpha nigrospina sp. nov., Cnipsomorpha polyspina sp. nov., Cnipsomorpha serratitibia sp. nov., Cnipsomorpha trituberculata sp. nov. and Cnipsomorpha viridis sp. nov. A key to the species and list of the species of Cnipsomorpha are provided.